Anaemia of Chronic Disease; A Study of Cases in a Tertiary Care Hospital - Muhammad Maaz , Muhammad Maaz; Muhammad Nauman Tariq, Muhammad Nauman Tariq; Hamza Waqar Bhatti , Hamza Waqar Bhatti; Nadeem Ikram, Nadeem Ikram (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Anaemia of chronic disease (ACD) is the second most prevalent type of anaemia. Causes can be chronic infections, autoimmune diseases, malignancies and is characterized by pathologic iron homeostasis, impaired erythropoiesis and blunted erythropoietin response. Materials and Methods: This retrospective case series study was conducted in Department of Pathology, Benazir Bhutto Hospital Rawalpindi where all the consecutive cases of ACD diagnosed by peripheral blood smear and bone marrow slide examination, presented during 2014-2016 were studied. The presenting complaints, physical examination findings, complete blood count, bone marrow biopsy, and provisional diagnosis were noted. Patients with other types of anaemia were excluded. Results: In our study of 51 cases, 27(52.9%) were males and 24(47%) were females. Median age was 35 years. Most common age group involved was 8-25 years (25.39%). Fever was the commonest complaint (68.6%) followed by weight loss (37.2%). Commonest physical examination finding was pallor (90.2%) and hepatomegaly (37.2%). Severe anaemia (Hb≤8g/dl) was present in 43.1% cases. RBCs were microcytic hypochromic in 43.1% of patients. Thrombocytopenia (platelets <150,000/mm3) was a finding in 49% of patients. Hemophagocytes were present in 49% of cases. Aetiology was undiagnosed in 68.6% of cases. 45.09% patients had a previous history of blood transfusion. Conclusion: Fever is the commonest presenting complaint. Most of the cases have unknown aetiology. A high number of patients with severe anaemia is not in accordance with ACD as a disease of mild anaemia. This reflects inappropriate recognition of ACD.